Study of Intrinsic Viscosity and Flow Activation Energy of Some Polymers in Different Solvents - Kashmoula, Talib B.; Ahmed, Rabab I. (Nahrain University College of Engineering Journal, 2017)
The intrinsic viscosity has been studied forseveral polymers which are used in someindustrial applications, such as polyisobutylene oftypes Oppanol B150, 200, and 250 with differentmolecular weights of 2.5, 4.1 and 5.9 milliong/mole, respectively, which dissolved in crudeand gas oil. In addition three types of additivesbrought from Al-Dura refinery, olefin copolymer(OCP), {viscoples-4-677, viscoplex-215496, andLubrizol R 7077} which dissolved in crude oil,and the polymers which is soluble in water suchas polyacrylamide with high molecular weightand xanthan gum with molecular weight 3.7million g/mole where also studied. It was foundthat the intrinsic viscosity of polyisobutylenedecrease as the temperature increase in crude andgas oil. The olefin copolymer (Viscoplex-4-677)showed the same behavior as polyisobutylenewhere it can be used as drag reduction agent. Itwas noted that neutral polymers as well aspolyelectrolytes could be used as drag reductionagent.